The use of Digital Signage as Media Campus Information (Penggunaan Digital Signage sebagai Media Informasi Kampus) - nfn Muhajirin; Wiflfridus Daryono (Jurnal Pekommas, 2018)
campus information is needed by the entire academic community. Information is updated in STMIK CMR presented in the form of images which are patched, running text, video, and broadcast television, but the information is presented in a separate media, so several parts should be visited to get the whole information. It results the information not spreading rapidly. Literature review and field research have been conducted. Data gaining is through system analysis, system design, and system implementation & testing. The results showed that the loading time has been relatively fast with the average value of 92%, the display system has been attractive with an average value of 90%, the ease of use of the system’s average value has been 84%, the ease in obtaining information from the campus’ average value has been 88 %, and the process of uploading photos, videos’ average value has been 92%. From the results, it can be concluded that the information boards already met the needs of the respondents, with an average value of 89.2%. It is why, the information board may be applied on campus as the center of informations or announcements, so that it would be easier for students and lecturers in gaining campus information.Informasi dalam kampus sangat dibutuhkan oleh seluruh civitas akademik. Penyajian informasi di STMIK AKBA telah mutakhir. Informasi tersebut disajikan dalam bentuk gambar yang ditempel, teks berjalan, video, dan siaran televisi. Akan tetapi informasi tersebut disajikan dalam media yang terpisah, sehingga harus mengunjungi beberapa bagian untuk mendapatkan informasi secara keseluruhan. Hal ini mengakibatkan informasi tidak menyebar secara cepat. Penelitian kepustakaan dan penelitian lapangan dengan metode pengumpulan data ini melalui tahap analisis sistem, desain sistem, implementasi dan pengujian sistem. Hasil menunjukkan bahwa waktu tunggu relatif cepat, yakni dengan nilai rata-rata 92%, tampilan sistem menarik dengan nilai rata-rata 90%, kemudahan dalam penggunaan sistem dengan nilai rata-rata 84%, kemudahan dalam mendapatkan informasi dari kampus dengan nilai rata-rata 88%, dan proses upload foto dan video dengan nilai rata-rata 92%. Dari hasil diatas, dapat disimpulkan bahwa papan informasi ini sudah memenuhi kebutuhan responden dengan nilai rata-rata 89.2%. Oleh sebab itu, papan informasi ini boleh diterapkan dikampus sebagai sarana informasi atau pengumuman kampus, sehingga memudahkan mahasiswa dan dosen dalam mendapatkan informasi kampus.